Development and validation of an algorithm for cardiomyocyte beating frequency determination - Wassermann, D. (2005)
The Chagas disease or Tripanosomiasis Americana affects between 16 and 18 million people in endemic areas. This disease affects the beating rate of infected patients' cardiomyocytes. At the Molecular Biology of Chagas Disease Laboratory in Argentina the effect of isolated patient's serum antibodies is studied over rat cardiomyocyte cultures. In this work an image processing application to measure the beating rate of this culture over video sequences is presented. This work is organized as follows. Firstly, a preliminary analysis of the problem is introduced, isolating the main characteristics of the problem. Secondly, a Monte Carlo experiment is designed and used to evaluate the robustness and validity of the algorithm. Finally, an algorithm of order O(T(N log N + N)) for tracking cardiomyocyte membranes is presented, where T is the number of frames and N is the maximum area of the membrane. Its performance is compared against the standard beating rate measure method. © Springer-Verlag Berlin Heidelberg 2005.